A bibliometric analysis of trends, challenges, and innovations in English teaching materials: A global review - Harni Jusuf; Hasan Ayuba; Alvons Habibie; Della Rachma Citra Prakasita (English Learning Innovation, 2025)
The rapid digital transformation in education has fundamentally altered the development of English Teaching Materials (ETM), especially in professional domains like tourism, healthcare, and hospitality, where context-specific language skills are crucial for effective global communication.  This study aims to analyze principal trends in ETM development over the last two decades, identify challenges encountered by researchers worldwide, examine the impact of technology and digitalization on ETM evolution, and assess the contribution of global ETM research to enhancing the quality of English language teaching in professional and specialized contexts.  A bibliometric study was conducted utilizing VOSviewer software to examine 204 publications from the Scopus database from 2000 to 2025, adhering to an adapted PRISMA methodology for bibliometric studies.  The data analysis encompassed co-occurrence terminology analysis, overlay visualization, and network mapping to discern thematic clusters, collaboration patterns, and temporal evolution dynamics.  The findings identify eight essential thematic clusters that reflect various research orientations: curricular architecture and education (notably in medical education), autonomous learning strategies, technology implementation, fundamental dimensions of English Language Teaching (ELT), English for Specific Purposes (ESP), holistic linguistic competence, research publication and quantitative investigation, and core thematic nexus.  The research reveals a significant publication increase, particularly intensifying around 2020, a geographic concentration with the Russian Federation as the dominant contributor, likely reflecting national investment in English for professional purposes, such as medical and tourism education and Tatarinova as the most prolific author, exemplifying institutional specialization and leadership in context-specific ETM research.  The temporal evolution indicates a distinct shift from curriculum-centric research (2016–2019) to technology-enhanced methodologies (2021–2024), likely accelerated by the COVID-19 pandemic and the global push toward digital transformation in education.  The study offers an extensive mapping of the ETM research landscape, focusing on professional applications, and gives strategic direction for creating successful, context-sensitive teaching materials that meet both global standardized requirements and local cultural contexts